In vitro Evaluation of Porous borosilicate, borophosphate and phosphate Bioactive Glasses Scaffolds fabricated using Foaming Agent for Bone Regeneration - Erasmus, E. P.; Sule, R.; Johnson, O. T.; Massera, J.; Sigalas, I. (Nature Research, 2018)
In this work, glasses within the borosilicate borophosphate and phosphate family were sintered into 3D porous scaffolds using 60 and 70 vol. % NH4(HCO3) as a foaming agent. All scaffolds produced remained amorphous; apart from one third of the glasses which crystallized. All produced scaffolds had porosity >50% and interconnected pores in the range of 250–570 μm; as evidenced by μCT. The in-vitro dissolution of the scaffolds in SBF and changes in compression were assessed as a function of immersion time. The pH of the solution containing the borosilicate scaffolds increased due to the typical noncongruent dissolution of this glass family. Borophosphate and phosphate scaffolds induced a decrease in pH upon dissolution attributed to the congruent dissolution of those materials and the large release of phosphate within the media. As prepared, scaffolds showed compressive strength of 1.29 ± 0.21, 1.56 ± 0.63, 3.63 ± 0.69 MPa for the borosilicate, borophosphate and phosphate samples sintered with 60 vol. % NH4 (HCO3), respectively. Evidence of hydroxyapatite precipitation on the borosilicate glass scaffolds was shown by SEM/EDS, XRD and ICP-OES analysis. The borophosphate scaffolds remained stable upon dissolution. The phosphate scaffolds were fully crystallized, leading to very large release of phosphate in the media.
Keywords: Bioinspired materials; Orthopaedics; SDG-17: Partnerships for the goals